2006
DOI: 10.1074/jbc.m604640200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Salmonella enterica Serovar Typhimurium Isolated from RAW 264.7 Macrophages

Abstract: To evade host resistance mechanisms, Salmonella enterica serovar Typhimurium (STM), a facultative intracellular pathogen, must alter its proteome following macrophage infection. To identify new colonization and virulence factors that mediate STM pathogenesis, we have isolated STM cells from RAW 264.7 macrophages at various time points following infection and used a liquid chromatography-mass spectrometry-based proteomic approach to detect the changes in STM protein abundance. Because host resistance to STM inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 57 publications
4
85
1
Order By: Relevance
“…Overall, our work significantly advanced quantitative proteomics of intracellular Salmonella, as only 315 bacterial proteins were measured previously (19). With ϳ3,300 proteins identified in total, our LC-MS-based approach covered ϳ73% of the Salmonella proteome, which contains ϳ4,500 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our work significantly advanced quantitative proteomics of intracellular Salmonella, as only 315 bacterial proteins were measured previously (19). With ϳ3,300 proteins identified in total, our LC-MS-based approach covered ϳ73% of the Salmonella proteome, which contains ϳ4,500 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Further mutational analyses revealed that most of these observed proteins/metabolic enzymes are nonessential for Salmonella virulence, suggesting robust bacterial metabolism and availability of diverse nutrients in the host. In the same year, Shi et al reported the first quantitative time course study of intracellular Salmonella proteome in infected macrophages (19). They found that 39 of 315 bacterial proteins were strongly induced after infection and, notably, that deletion of STM3117 led to markedly reduced replication, implicating STM3117 in a critical role in Salmonella colonization inside macrophages.…”
mentioning
confidence: 97%
“…This was significantly higher coverage relative to other literature reports for intracellular pathogens. For example, in a recent study of Salmonella enterica serovar Typhimurium recovered from macrophages, 315 proteins were detected and 39 were described as differentially regulated [42].…”
Section: Qualitative Proteome Coveragementioning
confidence: 99%
“…[3] The large excess of host proteins in mixed pathogen-host lysates presents a significant challenge for proteomic analysis of bacterial proteins during infections [3] and even after physical isolation of intact bacteria significant amounts of host proteins still remain. [4,5] This is particularly important since many bacterial virulence factors are often expressed at low levels. [2] New strategies are therefore required to selectively enrich bacterial proteins from host proteomes for their analysis during infection.…”
mentioning
confidence: 99%